If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(z + 2) + -3(z + -3) = 4(2 + -3) + 3(z + -1) Reorder the terms: 11(2 + z) + -3(z + -3) = 4(2 + -3) + 3(z + -1) (2 * 11 + z * 11) + -3(z + -3) = 4(2 + -3) + 3(z + -1) (22 + 11z) + -3(z + -3) = 4(2 + -3) + 3(z + -1) Reorder the terms: 22 + 11z + -3(-3 + z) = 4(2 + -3) + 3(z + -1) 22 + 11z + (-3 * -3 + z * -3) = 4(2 + -3) + 3(z + -1) 22 + 11z + (9 + -3z) = 4(2 + -3) + 3(z + -1) Reorder the terms: 22 + 9 + 11z + -3z = 4(2 + -3) + 3(z + -1) Combine like terms: 22 + 9 = 31 31 + 11z + -3z = 4(2 + -3) + 3(z + -1) Combine like terms: 11z + -3z = 8z 31 + 8z = 4(2 + -3) + 3(z + -1) Combine like terms: 2 + -3 = -1 31 + 8z = 4(-1) + 3(z + -1) Multiply 4 * -1 31 + 8z = -4 + 3(z + -1) Reorder the terms: 31 + 8z = -4 + 3(-1 + z) 31 + 8z = -4 + (-1 * 3 + z * 3) 31 + 8z = -4 + (-3 + 3z) Combine like terms: -4 + -3 = -7 31 + 8z = -7 + 3z Solving 31 + 8z = -7 + 3z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-3z' to each side of the equation. 31 + 8z + -3z = -7 + 3z + -3z Combine like terms: 8z + -3z = 5z 31 + 5z = -7 + 3z + -3z Combine like terms: 3z + -3z = 0 31 + 5z = -7 + 0 31 + 5z = -7 Add '-31' to each side of the equation. 31 + -31 + 5z = -7 + -31 Combine like terms: 31 + -31 = 0 0 + 5z = -7 + -31 5z = -7 + -31 Combine like terms: -7 + -31 = -38 5z = -38 Divide each side by '5'. z = -7.6 Simplifying z = -7.6
| y=14-(5x-8) | | -19=-5x+12 | | -15=-4n+5 | | x^3+12x^2-3x-910=0 | | 10x-91=-107 | | 240-12x+x*x=0 | | 17x-(8x-4)=13 | | 5/6y=-20 | | -3x/8=-3 | | 2(5z+2)-6=88 | | (5x/8y^3)^2 | | x+24.8=48.5 | | 5(5x-1)=100 | | 40-2x=-38 | | 4x+9x-6x=42+7 | | 23=8x-9 | | 8-3n=n+4 | | -15x-60=-120 | | 10r+4=104 | | 0r+4=104 | | x+9=38 | | logx^2=8 | | -4y-6=1-3y | | -4x/5=60 | | -x+-x+-x+2=-x+-x+8 | | c+9=38 | | 3n-8=n+4 | | 19y-9=18y+27 | | 15=15x | | 447.104448(1609375/2442527)=x | | 38=x-9 | | 447.104448(2442527/1609375)=x |